Goya: del absolutismo ilustrado a la libertad política - Antonio Elorza (Cahiers de Civilisation Espagnole Contemporaine)
This paper intends to fully place Goya’s painting within the evolution of enlightened thought, from criticism of the privileged classes, beginning with the clergy, to that of moral degradation at the time of Maria Luisa and de Godoy. In this perspective, his unfurling imagination refers to real monsters. «No dejes ninguno» / «Leave None of Them» is his response to the “divine reason” after 1812. The journey is long, but fundamentally constant, moving from tapestry cartoons showing illustrations supporting the Constitution, to its collapse in 1814, which opened the way for the Black Paintings.